Changes in the daily life experience of patients with obsessive-compulsive disorder following mindfulness-based cognitive therapy: Looking beyond symptom reduction using ecological momentary assessment. (April 2020) - Landmann, Sarah; Cludius, Barbara; Tuschen-Caffier, Brunna; Moritz, Steffen; Külz, Anne Katrin
Highlights: MBCT participation did not result in significant changes of daily life experienced positive and negative affect, distress associated with OC symptoms, or acceptance of momentary emotions. Results indicate decreased insight into the unreasonableness of OC symptoms in the MBCT group at post-treatment. However, momentary OC symptoms at post-treatment predicted higher insight in the MBCT group. The finding concerning changes of insight post MBCT warrants further investigation. Future research should explore if longer and/or more intense guidance is needed for this patient group. Abstract: The current study examines changes in daily life experiences following mindfulness-based cognitive therapy (MBCT) in a sample of 38 patients with obsessive-compulsive disorder (OCD) and residual symptoms following cognitive behavioral therapy (CBT). Participants were randomized to either an MBCT group ( n  = 17), or to a psychoeducational group (OCD-EP; n  = 21) as an active control condition. Both groups underwent ecological momentary assessment (EMA) six times a day for a period of six consecutive days pre- and posttreatment. Contrary to hypotheses, MBCT participation did not, when compared to OCD-EP, result in significant changes of positive affect, negative affect, acceptance of momentary emotions, or distress associated with obsessive-compulsive (OC) symptoms. In fact, insight into the unreasonableness of OC symptoms improved significantly more in the OCD-EP group compared to MBCT. However, in the MBCT group, the presence of momentary OC symptoms at post assessment predicted increased insight, which indicates an improved ability to detach from OC symptoms in the moments in which they occur. All in all, however, results do not indicate favorable changes in everyday life experiences of OCD patients following MBCT. Owing to the modest sample size, results must be considered preliminary. Implications and directions for future research are discussed.